(untitled) (World Economics and Finance Bulletin, 2024)
The article discusses the reasons for the increase in cases of smuggling of tobacco products, factors influencing their increase, smuggling channels, producing countries of these smuggled products, the effectiveness of measures to combat smuggling, the impact of the excise tax rate on the smuggling of tobacco products. It has been shown that not only smuggling, but also tobacco produced in our republic, the consumption of its products has a negative impact on the health of the population. At the same time, based on foreign experience, the article examines the possibilities of preventing the illegal entry of contraband products into the territory of our republic and makes recommendations